2016
DOI: 10.1016/j.meegid.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the genotype 1 genes and proteins of human Wa-like rotaviruses vs. porcine rotaviruses

Abstract: Group A rotaviruses (RVAs) are 11-segmented, double-stranded RNA viruses and important causes of gastroenteritis in the young of many animal species. Previous studies have suggested that human Wa-like RVAs share a close evolutionary relationship with porcine RVAs. Specifically, the VP1-VP3 and NSP2-5/6 genes of these viruses are usually classified as genotype 1 with >81% nucleotide sequence identity. Yet, it remains unknown whether the genotype 1 genes and proteins of human Wa-like strains are distinguishable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
(131 reference statements)
0
11
0
Order By: Relevance
“…RVs are widely distributed in Brazil, and have been described in animals (both young and adults) such as cattle 105 , birds 106 , and pigs 107,108 . In rodents, there is a single report of RVA associated with swine production 109 .…”
Section: /11mentioning
confidence: 99%
“…RVs are widely distributed in Brazil, and have been described in animals (both young and adults) such as cattle 105 , birds 106 , and pigs 107,108 . In rodents, there is a single report of RVA associated with swine production 109 .…”
Section: /11mentioning
confidence: 99%
“…A recent study found that backbone genes of genotype 1 human and porcine strains can be distinguished by conserved patterns of amino acid substitutions within the VP1, VP2, VP3, NSP1, NSP2, and NSP3 proteins33. We performed analysis on these five proteins from the strains sampled and compared results with the reference strains sampled in the publication (Figs 6 and 7).…”
Section: Resultsmentioning
confidence: 99%
“…All samples had NSP2 proteins that shared multiple conserved sites with Wa-like human origin NSP2 proteins but also had substitutions at positions 97 and 282 that resembled to patterns seen in porcine strains (D and L, respectively). Moreover, this combination of aa substitutions was detected in many reference human and porcine RVA strains33. Thus, the genesis of NSP2 is difficult to discern, as the particular variable site pattern found in this protein is shared among various porcine and human strains33.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations